Pengaruh Metode Bermain Peran Oleh Guru PAK Terhadap Keaktifan Belajar Siswa Kelas XI Di SMA Negeri 2 Tarutung Tahun Pembelajaran 2019/2020 - Pitriani, Christina (Areopagus : Jurnal Pendidikan Dan Teologi Kristen, 2020)
Abstract: The Effect of the role playing method by PAK teachers on the learning activeness students of class XI in SMA Negeri 2 Tarutung in the academic year 2019/2020, with the hypothesis that is positive and significant the role playing method by PAK teachers on the learning activeness students of class XI in SMA Negeri 2 Tarutung in the academic year 2019/2020.This research uses descriptive quantitative inferential, with the participation of all students of class XI in SMA Negeri 2 Tarutung who collected 278 students with a sample collecting 56 students. Data were collected with a closed questionnaire as many as 38 items compiled by the author based on variable indicators according to expert theory. The questionnaire trial was conducted on 30 students who were not research respondents and had tested their validity and reliability.The results of data analysis show that is a positive and significant the role playing method by PAK teachers on the learning activeness student of class XI in SMA Negeri 2 Tarutung in the academic year 2019/2020 with a coefficient of determination (r2) = 38,93% and a significant test of the effect is obtained FhitungFtabelof 36,864,02, meaning that Ho was rejected Ha was accepted. Key Words: Role Playing Method, Students Learning Activeness